Case Study: Cardiac sarcoidosis resolved with Mycobacterium avium paratuberculosis antibiotics (MAP) - Celler, Branko George (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: The author presents a clinical history and personal case study following his diagnosis of inactive sarcoidosis in 2004, followed by an acute episode of cardiac sarcoidosis (CS) in 2012 which resulted in complete heart block, cardiac myopathy, heart failure and insertion of an implantable cardioverter defibrillator (ICD) pacemaker. Methods: Following a detailed review of the clinical and scientific literature he concluded that sarcoidosis may be a mycobacterial infection and could be treated with anti-MAP antibiotic regime (1) developed to treat Crohn’s disease. Findings: After successful culture and identification of viable MAP in his blood, treatment with the MAP antibiotic regime for one year led to complete metabolic resolution of the previously avid cardiac sarcoidosis and no PET evidence of any metabolically active sarcoidosis anywhere. Such reversal of cardiac sarcoidosis has never previously been reported.